Anticariogenic potential of Ocimum sanctum: A narrative review - Shankkari , Siva; Ankola, Anil V.; Sankeshwari, Roopali M.; Parimala, Yuvarani Kandasamy; Ragu, Kavitha (Indian Journal of Integrative Medicine, 2025)
Dental caries is an oral disease that is prevalent globally. It is determined by diet, saliva composition, and oral flora, with Streptococcus mutans being the major contributor. Conventionally, prevention of dental caries is targeted at the control of cariogenic bacteria and maintaining the optimum pH of the oral cavity. However, adverse reactions like allergic reactions, toxicity, and antimicrobial resistance linked with synthetic compounds have prompted research into plant-based products. This review proposes to investigate the anticarcinogenic potential of Ocimum sanctum, whose multifaceted therapeutic properties in traditional medicine are well documented. The present narrative review was done comparing numerous in vitro and in vivo studies that investigated the antibacterial, anti-plaque, and salivary pH modulation actions of Ocimum sanctum. The review further investigated studies on dental products formulated from Ocimum sanctum. Several in vitro studies showed that ethanolic and aqueous extracts of Ocimum sanctum strongly inhibited cariogenic bacteria, particularly Streptococcus mutans, with zones of inhibition and low Minimum Inhibitory Concentration (MIC) values. Its use in mouthwashes, dentifrices, and restorative materials has yielded encouraging results equivalent to chlorhexidine. Considering the antibacterial and anticariogenic potential of Ocimum sanctum, it can be used be an alternative which is biocompatible and cost effective.